Influence of Hypoalbuminemia on Methotrexate Clearance in Children Receiving High Dose Methotrexate Therapy - Zehra Batool, Nuzhat Yasmeen, Rabia Tariq, Muhammad Wasim Khan, Hijab Shaheen (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Methotrexate, a structural counterpart of folic acid, is well recognized as a very efficacious pharmaceutical agent utilized in the treatment of several pediatric oncological conditions. A high-dose methotrexate is employed as a therapeutic intervention for a diverse range of malignant conditions including leukemia, lymphomas, and osteosarcoma. Hypoalbuminemia also decreases the methotrexate clearance leading to increased toxicity. Objective: To determine the frequency of side effects among patients receiving high dose methotrexate therapy based on baseline albumin levels. Study Design: A quasi-experimental trial was conducted at the Pakistan Institute of Medical Sciences, Islamabad, from January 1, 2023, to July 31, 2023. A total of thirty-four children receiving HDMTX were enrolled in the study. Albumin level, grade of liver toxicity, renal function tests, gastrointestinal and neurological toxicity, and mucositis were noted. Length of stay and methotrexate level at 24 hours were also noted. All the information was recorded in proforma. Results: In this study, we included 34 children with a mean age of 6.29 ± 2.97 years. Out of 34 children, there were 24 (70.6%) male children, while 10 (29.4%) were female children. The most common diagnosis was leukemia [14 (41.2%)], followed by non-Hodgkin lymphoma [9 (26.5%)], leukemia relapse [6 (17.6%)], and osteoarthritis [5 (14.7%)]. The albumin level was low in 11 (32.4%) children while normal in 23 (67.6%) children. Toxicities were compared in children with low and normal albumin levels. Hepatotoxicities and gastrointestinal toxicities were insignificant between both groups (p > 0.05). But myelosuppresion and mucositis significantly showed higher grades in low albumin groups. Nephrotoxicity and neurological toxicities were only noted in children with low albumin groups, while no patients in normal albumin groups had neurological or nephrotoxicity. The mean length of stay of low albumin level children was longer than that of normal albumin level children (7.45 ± 3.24 vs. 4.17 ± 3.39 days, p<0.05), and the mean methotrexate level after 24 hours was also significantly higher (p<0.05) in the low albumin group (69.22 ± 97.40) than the normal albumin level (0.40 ± 1.14). Practical Implication: This would not only lessen toxicity but also enhance children’s health and quality of life. Before starting high-dose methotrexate (HDMTX) cycles, serum albumin levels should be evaluated. This is especially important in low-resource areas where malnutrition is common and serum methotrexate (MTX) monitoring may not be available. Conclusion: In this study, we conclude that hypoalbuminemia therapy has an effect on the reduction of hospital stays and methotrexate toxicity in high-risk children. In the future, we can recommend adding hypoalbuminemia therapy to reduce the toxicities of HDMTX. Keywords: High dose methotrexate therapy, albumin levels, renal function test, gastrointestinal toxicity, neurological toxicity, mucositis.